KAJIAN EKONOMI PEMANFAATAN KAYU UNTUK BARANG KERAJINAN - Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Processing of wood for handycraft is one way to increase added value through belier wood utilization. Research on wood handycraft was in Central Java. The study indicated that total added value for eight kind of product is Rp. 23.355,000 for every m3 input. Although cost of production increased up to Rp. 11.005.550 for every m3 input the profit increase to Rp. 7.202.000 for every m3 input leaving handycarft in a better off situation. The profit depend on the cost of production.Abded value were distributed into various factory variables such as overhead 12, 67 percent, labour 40.44 percent. materials 7.30 percent and management 39,56 percent.Total employment absorbed in producing all products were 29.290 mandays or 205.030man hours a year. However, handycraft industry were facmg various problems. aspecially on raw materials and capital.